Comparative safety analysis of lacosamide and perampanel in epilepsy management: insights from FAERS database - Ge, Chang; Jin, Liuyin; Tian, Jing-Jing; Yang, Na; Xu, Jian (Frontiers in Pharmacology, 2024)
Background: Epilepsy is a chronic neurological condition requiring effective management with minimal adverse effects. Lacosamide(LCM) and Perampanel(PER), two promising treatments, have distinct profiles that merit comparative analysis to guide clinical decision-making.Methods: This study utilizes a pharmacovigilance analysis of adverse events (AEs) reported in the FDA Adverse Event Reporting System (FAERS) database from Q1 2009 to Q3 2023. Employing disproportionality and Bayesian analyses, we assessed and compared the AE signals associated with LCM and PER to elucidate their safety profiles in epilepsy treatment.The analysis included 12,576 AE reports for LCM and 2,703 for PER, highlighting a higher incidence of psychiatric disorders, including aggression with LCM, and a notable association of PER with psychiatric disorders such as psychotic disorders and dizziness. LCM showed a relatively safe profile during pregnancy, whereas PER's data suggested caution due to reported cases of suicidal ideation and attempts.Conclusions: This comprehensive evaluation underscores the importance of understanding the distinct AE profiles of LCM and PER in clinical practice, providing valuable insights for personalized epilepsy management. Future research with rigorous prospective designs is recommended to validate these findings and explore the mechanisms underlying the reported adverse events.